The need for learning bioethics and law for biology students - Chan, Aaron Hin-tat; Whitton, Brian A.; Chan, Gilbert Y. S. (Journal of Biological Education, 2020)
Although the creation in 2018 of a pair of genome-edited HIV-resistant twins in China caused widespread condemnation, we question whether the law and ethics relevant to such cases are dealt with adequately in university programmes. Biology educators are entrusted with upholding the discipline’s standards, but are they doing enough to guide students towards ethical and law-abiding practices? As it seems likely that events such as the recent COVID-19 outbreak will increasingly focus public attention on issues of research integrity and biosecurity, we assessed the world’s top 20 undergraduate programmes in biology published by Quacquarelli Symonds. Most of these appear to lack any interaction between biology and law/ethics and the factual training for the next generation. Suggestions are made to improve teaching and learning processes in biological education.
Keywords: Bioethics; COVID-19; biosecurity; law; undergraduate curriculum